Molecular Epidemiology of Human Adenovirus, Astrovirus, and Sapovirus Among Outpatient Children With Acute Diarrhea in Chongqing, China, 2017–2019 - Tang, Xiang; Hu, Yue; Zhong, Xiaoni; Xu, Hongmei (Frontiers in Pediatrics, 2022)
Objective To investigate the epidemiology of human adenovirus (HAdV), human astrovirus (HAstV) and sapovirus (SaV), children with acute diarrhea in Chongqing, China from 2017 to 2019 were enrolled. Improved surveillance could provide better guidance for diarrhea prevention. Methods Between 2017 and 2019, fecal specimens were collected from children <14 years of age presenting with acute diarrhea for treatment at the outpatient department of the Children’s Hospital, Chongqing Medical University. Human HAdV in the fecal specimens was detected by PCR, while RT-PCR was adopted for the detection of HAstV and SaV. Results A total of 1352 fecal specimens were screened in this study. The detection rate of HAdV was 4.44% (60/1352), HAstV was 2.81% (38/1352) and SaV was 1.04% (14/1352). The prevalence of enteric viruses in males was not significantly different to females (p>0.05). We found 96.67% (58/60) of the HAdV-positive cases, 92.11% (35/38) of the HAstV-positive cases, and 100% (14/14) of the SaV-positive cases among the children under 4 years old. HAdV cases were identified throughout the year, while the infection of HAstV peaked from March to May every year. By contrast, SaV was detected in May, July, and from September to December. In total, 41 strains of HAdV-F were identified, including F41 (39/60) and F40 (2/60). Furthermore, A31, B3, B7, C1, C2, C5, C6 were also detected in the study. In addition, we detected two genotypes of HAstV, HAstV-1 (34/38) and HAstV-5 (4/38), and two genotypes of SaV, GⅠ.1 (13/14), GⅠ.2 (1/14). Conclusion The enteric viruses HAdV, HAstV and SaV contribute to the overall burden of diarrhea in Chongqing, especially in children <4 years of age. Two genotypes were identified for HAstV (HAstV-1 and HAstV-5) and SaV (GI.1 and GI.2) with an additional nine genotypes detected in HAdV cases. While the F41 HAdV strain was predominant, HAdV-A31 was also detected in 10% of cases. The study results along with continuous surveillance of enteric viruses will aid in the design and implementation of future enteric vaccines and diarrhea mitigation strategies.